ISLAM DAN KEMAJEMUKAN DI INDONESIA (Upaya Menjadikan Nilai-nilai yang Menjunjung Tinggi Kemajemukan dalam Islam sebagai Kekuatan Positif bagi Perkembangan Demokrasi): Islam and Pluralism in Indonesia: Upholding Diversity as a Positive Force in Democratic Development - Syarif, Nurrohman (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
Indonesia is a pluralistic nation when seen from diverse ethnic, cultural, linguistic, ethnic and religious diversity as a result of it is likely to have a positive impact or negative. Pluralism in Islamic thought caused by the many schools of theology, jurisprudence flow or Islamic law, schools of philosophy, mysticism or the mysticism and political currents. In this paper, the authors focus on explaining some of the factors that hinder the development of pluralism in Indonesia, which is associated with the concept of the protection of religion, the concept of ‘amar ma‘ruf nahyi munkar, the concept nasakh-mansukh, other threats to diversity is the rise of authoritarianism in the interpretation of religion, lack of enforcement law from law enforcement officials in Indonesia, and the weakness of education and understanding among Muslims toward religion.